Characterization and evolution of the coefficient of friction during pin on disc tribotest: Comparison between C10200 Cu, AA6082-T6 Al and C36000 brass pins under varying normal loads. (October 2019) - Ferreira, R.O.; Galvani, G.B.; Tertuliano, I.S.; Rodrigues, A.C.P.; Azevedo, C.R.F.
Abstract: Cu, leaded α+β brass and Al-alloy pins were pin-on-disc (PoD) tested against steel discs using sliding speed of 0.1 m/s and contact pressures from 0.51 to 2.55 MPa. Cu/steel tribopair showed unstable coefficient of friction (CoF) evolution around 0.6, while Al/steel and brass/steel tribopairs featured stable CoF evolution, around 0.42 and 0.30 respectively. The tribosurfaces of the discs and pins were characterized by laser interferometry and microscopy. Cu/steel and Al-alloy/steel tribopairs presented oxide transfer films, but intense adhesion of Cu on the discs produced unstable CoF evolution of the Cu/steel tribopair. Conversely, intense leaded-brass adhesion promoted the lowest and more stable CoF evolution of the brass/steel tribopair. Highlights: Pin on disc tests assessed the friction coefficient evolution of 3 tribopairs. Cu/steel presented unstable CoF evolution, with average value of 0.65. Al alloy/steel presented stable CoF evolution, with average value of 0.42. Brass/steel presented stable CoF evolution, with average value of 0.30. Tribosurfaces and tribolayers were characterized to explain CoF values and behaviour.